Cruciate ligament loading during isometric muscle contractions. A theoretical basis for rehabilitation. - Zavatsky, A; Beard, D; O'Connor, J (1994)
A model of the knee in the sagittal plane was used to investigate the ligament forces resulting when an external load applied to the tibia resisted either extension or flexion of the knee under increasing isometric quadriceps or hamstrings contractions, respectively. An elementary mechanical analysis showed which ligament, the anterior or posterior cruciate, was loaded at a given flexion angle and known line of action of the external load. Ligament force, as a proportion of the external load, was also calculated. The results serve as guidelines for the design of injury-specific physical therapy techniques for use after cruciate ligament reconstruction.